2010
DOI: 10.1177/1477370809358018
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported youth delinquency in Europe and beyond: First results of the Second International Self-Report Delinquency Study in the context of police and victimization data

Abstract: This article reports on the first results of the Second International Self-Report Delinquency Study (ISRD-2), a large international collaborative study of delinquency and victimization of 12—15-year-old students. The analysis is based on a subsample of the data set: 43,968 respondents from 63 cities and 31 countries. The prevalence rates of the major categories of delinquency, both for individual countries as well as for 6 country clusters, are presented as well as data for victimization experiences (theft and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 11 publications
0
80
0
4
Order By: Relevance
“…The Nordic countries have shown to have many similarities in youth victimization studies [9] but especially related to parental maltreatment, countries also have remarkable differences. Although across the Nordic countries, violence and maltreatment have been rather strictly defined and legislated against, there is a major difference between the two countries included in this study regarding the time when corporal punishment was made a penal act.…”
mentioning
confidence: 99%
“…The Nordic countries have shown to have many similarities in youth victimization studies [9] but especially related to parental maltreatment, countries also have remarkable differences. Although across the Nordic countries, violence and maltreatment have been rather strictly defined and legislated against, there is a major difference between the two countries included in this study regarding the time when corporal punishment was made a penal act.…”
mentioning
confidence: 99%
“…We are unaware of any similar previous work that has linked the two in this manner as most comparative scholarship based on self-reported data has been largely descriptive (e.g., Enzmann et al, 2010) or it has exclusively focused on predictors and dependent measures based on country-level, official data (Pridemore, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Switzerland (e.g., Clinard, 1978) and Japan (Komiya, 1999;cf., Kobayashi, Vazsonyi, Chen, & Sharp, 2010), for example, are regarded as having comparatively few problems with young people violating social norms, local mores, and laws. However, most recent scholarship and theorizing about the etiology of crime and deviance (e.g., self-control theory, Gottfredson & Hirschi, 1990), including cross-national comparative work focused mostly on individual-level or selfreported perpetration or victimization data (Enzmann et al, 2010;Vazsonyi & Belliston, 2007;Vazsonyi, Pickering, Hessing, & Junger, 2001), suggest that the problem of crime and deviance exists within most -if not all -human societies. This is certainly true of the data collected as part of the International Self-report Delinquency Study (ISRD), which most recently included 31 countries (Enzmann et al, 2010), mostly European ones, and which as an initial step has documented fairly large variability in rates of delinquency across cultures, but also some degree of overlap between self-reported delinquency and measures of victimization from other data sources.…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, these rates were much smaller ranging between 3% for the 13 and 15 year old Norwegian girls and 10.7% for the 13 year old Norwegian boys and 11.3% for the 15 year old Norwegian boys. Another important source of comparative data is the Second International Self Reported Delinquency Study, ISRD-2 (Enzmann et al, 2010). This study reported the 12 month prevalence rates of self reported delinquency measured by 12 differently serious offences in 31 countries.…”
Section: Levels Of Bullying In Schools In Austria and Norwaymentioning
confidence: 99%